2022
DOI: 10.3390/biom12020171
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Amino Acid Recruitment Order in Early Life by Genome-Wide Analysis of Amino Acid Usage Bias

Abstract: The mechanisms shaping the amino acids recruitment pattern into the proteins in the early life history presently remains a huge mystery. In this study, we conducted genome-wide analyses of amino acids usage and genetic codons structure in 7270 species across three domains of life. The carried-out analyses evidenced ubiquitous usage bias of amino acids that were likely independent from codon usage bias. Taking advantage of codon usage bias, we performed pseudotime analysis to re-determine the chronological orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…For instance, considering microorganisms from several extreme habitats, it was suggested that microbes that could survive in a wide range of habitats exhibit high CUB 2 . An environment-specific trend has also been noticed in the relative usage of different AAs 5 7 , 23 , 24 . However, most of these studies were conducted at the species level considering genomes of cultured microorganisms precluding the community effect.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…For instance, considering microorganisms from several extreme habitats, it was suggested that microbes that could survive in a wide range of habitats exhibit high CUB 2 . An environment-specific trend has also been noticed in the relative usage of different AAs 5 7 , 23 , 24 . However, most of these studies were conducted at the species level considering genomes of cultured microorganisms precluding the community effect.…”
Section: Introductionmentioning
confidence: 85%
“…The environment where the microbes populate was suggested to influence every aspect of the microbial genome, including their codon and AA choice. Following this, previous studies speculated that codon or AA usage might be associated with the lifestyle of the organism 1 10 , 23 , 24 . For instance, considering microorganisms from several extreme habitats, it was suggested that microbes that could survive in a wide range of habitats exhibit high CUB 2 .…”
Section: Introductionmentioning
confidence: 89%
“…Some of the components of the anteome of the SL biosynthetic pathway (Fig. 2) have been proposed as components of metabolic pathways that may have existed in the last universal common ancestor (LUCA) (the most recent organism from which all existing organisms appear to share common descent), including PLP-dependent enzymes, L-serine, L-alanine, NADPH and CoA [114,[122][123][124]. However, as suggestive as the appearance of these anteome components is, genes encoding enzymes of the SL pathway have not been proposed to exist in LUCA, indicating that the evolution of the pathway must have happened later.…”
Section: Co-evolution Of the Sl De Novo Biosynthetic Pathway And Anteomementioning
confidence: 99%